Assessing the Implementation of the New Early Childhood Care and Development (ECCD) Accreditation in Silvino Lubos, Northern Samar, Philippines - Sagonoy, Agner S. (International Journal of Research in Interdisciplinary Studies, 2025)
This qualitative inquiry examined the implementation of the Early Childhood Care and Development (ECCD) Program of the Municipal Social Welfare and Development Office (MSWDO) of Silvino Lubos, Northern Samar, Philippines using the National ECCD Accreditation Tool as the primary evaluative framework. Exploring readiness and challenges, and contextual barriers of child development service delivery conducted across 26 barangays of Silvino Lubos, a GIDA area, face perennial inadequacies in resources, politics, infrastructures and varied capacities. The study explored the contextual barriers and alignment with the national standards as well as implementation readiness using key informant interviews, focus group discussions (FGD), and document review. Through thematic analysis, four key concerns were raised: (1) structural or infrastructure and resources deficiencies, (2) political barriers to prioritization and motivation of a workforce, (3) differences in training and inadequate qualifications of Child Development Workers (CDWs), and (4) the national ECCD standards and the LGUs and barangays colliding gaps in resources. Findings indicate that Child Development Centers remain unaccredited due to inadequate facilities, irregular honoraria and incomplete documentation. A critical gap was also identified between ECCD curriculum implementation (ages 0–4) under LGUs and the Department of Education’s Kindergarten program (age 5), resulting in discontinuities in school readiness and learning transitions. The study recommends contextualized accreditation for GIDAs, strengthened workforce professionalization of Child Development Workers and supervisors, political-neutral governance mechanisms, infrastructure investment, and improved coordination between ECCD providers and DepEd to ensure continuity of early learning. For the University of Eastern Philippines, the findings provide empirical evidence to inform policy-oriented research, enrich instruction in social development, education, and public administration programs, and strengthen extension initiatives that support LGUs in designing context-sensitive ECCD interventions for marginalized and GIDA communities.